Perceptions of "Incurable" Diseases and Therapeutic Responses among Traditional Healers in the District of Abidjan - Adiko, Adiko Francis; N’Goran, Kouakou Gérard; Koua, Kouakou Adrien (Advances in Social Sciences Research Journal, 2022)
In Africa and particularly in Côte d’Ivoire, traditional medicine highlights the consideration of the association between biological, psychological and social factors within the framework of public health policies. But in reality, it is clear that there is a neglect of the psychosocial dimension in favor of the biomedical aspects, even on the part of traditional healers in the management of incurable diseases. Indeed, traditional medicine seems to be part of a process of reduction to phytotherapy drugs while ignoring its cultural basis. The question is to know which posture and which approach appear to be the most appropriate in the evaluation, prevention and treatment of complex diseases. The objective of this research is to describe and analyze the perceptions of the causes of so-called "incurable" diseases and the therapeutic responses proposed by traditional healers. The methodology was based on documentary research and semi-structured interviews with 30 traditional healers in the district of Abidjan. The results show that the perception of causes and therapeutic responses are surrounded by complexity. This research has therefore highlighted the fact that people with an incurable disease are considered by traditional healers as people in need of psychosocial care. Ultimately, it should be noted that traditional medicine offers an alternative response to the management of so-called incurable diseases in the district of Abidjan. These characteristics of the perception of causes and therapeutic responses are parameters to be considered in the management of so-called incurable diseases in African society.